What motivate us: a critical review of the book Payoff: The Hidden Logic That Shapes Our Motivations - Ben, Rodrigo Dan (Perspectivas em Análise do Comportamento, 2017)
Motivation is present in everything we do. With this assumption, Dan Arielys’ new book presents how we can destroy motivation, feel pleased by doing something ourselves, how different kinds of consequences alter motivation, and how motivation extend beyond individual existence. The book contains several everyday examples and the arguments can be understood intuitively, but the scarce empirical basis limits the arguments’ generality and reliability.